Creation of “Salen-Log Counterpoint”: intercultural music between karawitan and orchestra through practice based research - Nugraha, Aditya; Sukmayadi, Yudi; Riyadi, Lanang (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
This study explores the process of creating a musical composition titled